A Simple Strategy for Multi-Material Diffusion and Its Application to Three-Temperature Multi-Material Flows (Communications in Computational Physics, 2025)
This work is devoted to the numerical approximation of three-temperaturemulti-material hydrodynamics. Such systems are subject to stiff phenomena which require specific care during the discretization. In particular, the so-called discrete equation method is here applied to the radiation transport, in the optically-thick limit. Thisstrategy is shown to be accurate in the presence of in-cell interfaces while being simplerthan standard interface reconstruction techniques. It is then incorporated into a three-temperature multi-material scheme whose implicit temporal discretization is based onconvex combinations. Stiff test cases eventually establish the scheme’s robustness.
Keywords: Numerical scheme; diffusion equation; multi-material flows; radiation hydrodynamics; plasma physics.